Percepção das condições higiênico-sanitárias e físicoestruturais da área de manipulação de proteínas de origem animal in natura, em um mercado público do município de Coari- AM - Parente, Suzimar Guimarães (Brasil, 2020)
Data of OMS show that foodborne diseases are assessed as the biggest public health problem worldwide and the handlers referred to as the main contamination vehicles, as their participation reaches up to 26% of the contaminating sources (LUNDGREN, et al., 2009). Thus, this work aimed to analyze the hygienic-sanitary and physical-variable conditions in the area of manipulation of proteins of animal origin in natura, in a public market in the municipality of Coari-AM. They were analyzed as hygienic conditions and physical structure through a descriptive observatory field study, used as a tool, a Checklist prepared according to RDC nº 275/2002. An area of manipulation and commercialization of animal proteins in natura on the market is not in compliance with the resolution, as throughout the investigation there were several irregularities. It is known, however, that it is of fundamental importance to guarantee the quality of proteins in compliance with current legislation with regard to the correct handling of food. As a result, commercialized products will not become sources of infections transmitted by poorly handled and / or commercialized foods. In addition, it was observed that in the market researched there is a need for public policies aimed at health issues, in order for hygienic-sanitary and physical conditions to alter the researched location.